NARRATIVE REVIEW ON THE CLINICAL PRACTICE GUIDELINES FOR THE MANAGEMENT OF OVERWEIGHT/OBESITY IN ADULTS - AMIRTHALINGAM, PALANISAMY (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objectives: Obesity causes morbidity and mortality and also impairs the quality of life in humans. Clinical practice guidelines are well established to treat the obese population with or without comorbidities in all the age groups. Obesity in adults is a risk factor for metabolic disorders including Type-2 diabetes mellitus, hypertension, dyslipidemia, etc. Hence, this review has compared the various international clinical practice guidelines for the management of obesity in adults. Methods: Four articles were included in the qualitative synthesis after the systematic review of the literature obtained from PubMed/MEDLINE and Web of Sciences. Diagnosis and various interventions including lifestyle, pharmacotherapy and bariatric surgery are compared for the management of obesity in adults. Results: The diagnosis is crucial since the criteria to determine overweight/obesity is still under debate due to inconclusive evidence. Various interventions including diet, exercise, behavior, drug therapy, and surgery are being recommended currently for the management of obesity. However, ethnicity and culture play a major role in diagnosis and also interventions. Moreover, personalizing the interventions according to the subject will make sense and offers success in the management of obesity. Conclusion: Diagnosis and the intervention should be subject oriented based on ethnicity, culture and patient characteristics. In this connection, many longitudinal studies warranted to specify the diagnostic and management criteria for adults among the various ethnic populations across the world.